BINAHONG [Anredera cordifolia (Tenore) Steenis] LEAF INFUSA FOR SUTURE WOUND INFECTION CONVALESCENCE - Baso, Siti Nur Azizah Sucitra; Azizah, Nurul; Rosyidah, Rafhani; Rinata, Evi (UNIVERSITAS AIRLANGGA, 2023)
Background: Postpartum infections are the top 4 main causes of the high maternal mortality rate in Indonesia at 2022 of 183 per 100,000 live births. Efforts to prevent complications due to infection of puerperal suture wounds with pharmacological therapy using antibiotics and antiseptics, as well as non-pharmacological ones using plant extracts. Binahong is believed to contain flavonoids, terpenoids, saponins, tannins, essential oils, and alkaloids, which are especially useful in healing wound infections. The aim of the study was to determine the effectiveness of infusion of binahong leaves (Anredera cordifolia (Tenore) Steenis) on the healing of suture wound infections in rats (Rattus norvegicus) experimental animals. Method: The research method was a true-experimental posttest only control group design, the study was conducted from June to August 2023 at the Microbiology and Pharmacology Laboratory of Muhammadiyah Sidoarjo University, the research variables were binahong leaf infusion and healing of suture infection, assessment and data collection using the REEDA scale instrument, statistical analysis with the one-way ANOVA, and post-hoc follow-up tests. Result: The results showed p <0.05, so there was a significant effect of giving binahong leaf infusion on the healing of suture wound infections. In terms of the difference in the mean value and the results of the post-hoc significant difference test, it appears that the 5% binahong leaf infusion group showed the most effective results in healing suture wound infections and was significantly different from the negative control group with less effective healing of suture infections. Conclusion : This is in line with research that states that the group given a 5% concentration of binahong extract was more effective than the group with a higher concentration. Thus, administration of a 5% concentration of binahong leaf infusion can be an alternative for healing suture wound infections due to the important content in it in the form of flavonoids, terpenoids, saponins, tannins, essential oils, and alkaloids. Further research is needed with lower concentrations of binahong leaf infusion to find out the minimum concentration that can have a good effect on the convalescence of suture wound infections.